The Correlation between Teacher Professional Competence and Natural Science Learning Achievement in Elementary School - I Ketut Ngurah Ardiawan (Universitas Negeri Makassar, 2017)
This present study aims at investigating the correlation between teachers’ professional competence and natural science learning achievement in elementary schools in Buleleng regency. The population in this study are all sixth grade teachers, which it is further narrowed down to 30 teachers as the sample. In order to gather the data, the researcher employs questionnaire regarding teacher professional competence and document study toward students’ achievement on national examination in academic year 2016/2017. Further, ex post facto is chosen as the design of the study. Meanwhile, the data are analysed through correlation analysis with assistance of SPSS 16 software. Based on the analysis, it was obtained that the correlation between teacher professional competence and the learning achievement on natural science subject is in the interval of 0.40-0.59 with correlation coefficient at rho=0.506. This means there is a significant correlation between teacher professional competence and students’ learning achievement on natural science in national examination in academic year 2016/2017 (tcount = 3.103 > ttable =2.048 with significance level at α = 0,05 and coefficient of determination at 0.2560 (25.60%)